THE STUDENTS’ PERCEPTIONS OF L1 USE IN TEACHING ENGLISH GRAMMAR - Retno Puspitasari (UICELL, 2021)
As grammar or structure is part of English lesson, it is important to find out why the students seem difficult to understand about it. Some of them even do not like this grammar material. The use of L1 could be one of the solutions for this problem. This research is aimed to view the students’ perceptions of L1 use in teaching grammar. The instruments used in the research were questionnaire and interview to senior high school students. The results show that 91.4% of the students had positive response to the use of L1 in teaching English grammar since it will help them to understand English grammar. Yet, the reason for those who gave negative response should also be considered before using L1 in teaching English grammar. Keywords: English grammar, L1 use, teaching English grammar, students’ perception